Increase of Nitrogenase Activity in the Blue-Green Alga Nostoc muscorum (Cyanobacterium) - Scherer, Siegfried (J Bacteriol, 1980)
Preincubation of the blue-green alga (cyanobacterium) Nostoc muscorum under hydrogen or argon (nongrowing conditions, neither CO(2) nor N(2) or bound nitrogen present) in the light resulted in a two- to fourfold increase of light-induced hydrogen evolution and a 30% increase of acetylene reduction. Preincubation under the same gases in the dark led to a decrease of both activities. Cultivation of algae under a hydrogen-containing atmosphere (N(2), H(2), CO(2)) increased neither hydrogen nor ethylene evolution by the cells. Formation of both ethylene and hydrogen is due to nitrogenase activity, which apparently was induced by the absence of N(2) or bound nitrogen and not by the presence of hydrogen. Inhibitors of protein biosynthesis prevented the increase of nitrogenase activity. Hydrogen uptake by the cells was almost unaffected under all of these conditions. With either ammonia or chloramphenicol present, nitrogenase activity decreased under growing conditions (i.e., an atmosphere of N(2) and CO(2)). The kinetics of decrease were the same with ammonia or chloramphenicol, which was interpreted as being due to rapid protein breakdown with a half-life of approximately 4 h. The decay of nitrogenase activity caused by chloramphenicol could be counteracted by nitrogenase-inducing conditions, i.e., by the absence of N(2) or bound nitrogen. A cell-free system from preconditioned algae with an adenosine 5′-triphosphate-generating system exhibited the same increase or decrease of nitrogenase activity as the intact cell filaments, indicating that this effect resided in the nitrogenase complex only. We tentatively assume that not the whole nitrogenase complex, but merely a subunit or a special protein with regulatory function, is susceptible to fast turnover.